Sustainable Eco-Print Entrepreneurial Motivations, Orientations, And Strategy Adoption of Women Entrepreneurs in Bekasi City, Indonesia - Lufina Mahadewi (Indonesian Journal of Sustainability Accounting and Management, 2024)
This research aims to reveal the practice of sustainable entrepreneurship in the context of motivational factors, sustainable entrepreneurial orientations, and the sustainable strategies undertaken to adopt a successful sustainable entrepreneurship carried out by women entrepreneurs in the Eco-Print business in Bekasi City, Indonesia. This research used the Interpretive case study design. It involved of conducting in-depth interviews to reveal intentional information with two Eco-Print women entrepreneurs in Bekasi City. The case studies are used to understand the motives and meaning of women entrepreneurs' actions that underlie the formation of an Eco-Print business, sustainable entrepreneurial orientations, and sustainable entrepreneurial strategies. The findings of this research signify the construction of a contingency framework of motivational factors, sustainable entrepreneurial orientations, and sustainable strategies realized by women entrepreneurs in Eco-Print through an entrepreneurial performance perspective. This research reveals the role of social identity theory in the form of community and sustainable entrepreneurial practices of women entrepreneurs in the adoption of strategies for entrepreneurial performance. This research signifies the conceptual development framework of the institutional arguments approach in the perspective of sustainable orientations of women entrepreneurs through sustainable entrepreneurship institutional activities and practices in the Eco-Print business.